(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: To describe the quality of life and to identify some factors related to the quality of life of patients with chronic obstructive pulmonary disease. Methods: A cross-sectional descriptive study was conducted, using the CAT toolkit to evaluate patients’ quality of life on 121 patients with chronic obstructive pulmonary disease at the Department of General Internal Medicine 1, Saint Paul General Hospital from August 2022 to December 2022. After cleaning, 90 survey forms were included in analysis. Results: The study showed that the average overall quality of life score was 22.22 ± 4.49, with 54.4% of patients experiencing a severely impacted quality of life due to chronic obstructive pulmonary disease. There was a statistically significant difference in the average quality of life scores according to the CAT scale in relation to BMI and disease duration among the patients. Conclusion: The quality of life for patients with chronic obstructive pulmonary disease is significantly affected, ranging from moderate to very severe. Therefore, it is crucial to pay attention in caring for patients with a BMI < 18.5 kg/m2 and/or a disease duration of more than 5 years to support the improvement of their overall health and enhance their quality of life.